Benefit assessment of second-life electric vehicle lithium-ion batteries in distributed power grid applications. (15th December 2022) - Song, Ziyou; Nazir, Md Salman; Cui, Xiaofan; Hiskens, Ian A.; Hofmann, Heath
Abstract: Lithium-ion batteries in electric vehicles (EVs) are typically replaced after they lose about 20% of their capacity. With the rapid growth in EVs, there will be a tremendous potential to re-use the remaining EV battery capacities in power systems. Hence, this work focuses on capturing the economic benefits of using such second-life (SL) EV batteries. While previous works mainly focus on bulk storage applications, we demonstrate that the most beneficial route for SL batteries lies in distributed applications in power systems. Specifically, refurbishment and grouping of SL battery packs pose technical and operational challenges, thereby incurring significant costs and risks when large battery packs are adopted in bulk applications. Instead, when distributed at the residential and micro-grid level, such refurbishment costs and operation risks can easily be avoided as only small-size battery packs are required. An experimentally-validated model is incorporated to capture the battery capacity degradation and used to compare fresh batteries and SL-batteries. Using a model predictive control scheme and a 33-bus power network, the benefits of SL-batteries are quantified and verified. Highlights: Second-life and fresh batteries are economically compared. Economic feasibility of used batteries is quantified in distributed power systems. Battery degradation cost is carefully incorporated in the analysis. Second-life batteries outperform the fresh ones in distributed power systems.